Comparative Analysis of Conventional and Plates Floor plate Floor Area Bondek PIM 3 Basement Project and Cost Performance Against Time - Hamonangan, Girsang; Khalid, Ihsan (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2020)
Work on the project floor Pondok Indah Mall 3 using plates bondek on basementnya area. Here I want to compare the effectiveness of the cost and time, why the owner and the contractor chose to use a plate bondek the basement area. This study aims to determine the differences of the two methods in terms of cost and time of work on the basement floor plates only at Pondok Indah Mall 3 project. Techniques of data collection using interviews and direct observations and combined with literature studies. Processing data using analytical methods of unit price (AHSP). The results of this research review time and cost. Observed work item is a work in basement slab. From this research work price obtained slab bondek system more expensive Rp 1,179,138,501 compared with the conventional method, in which the total price of the floor slab work bondek system is Rp 61,546,996,028, while the conventional method seberar Rp 60,367,857,526 As for the floor turnaround times bondek system requires 378 days, while the floor of conventional systems require 504 days.